(untitled) (Third Sector Social Economic Review, 2014)
In this study, entrepreneurial potential of students, who are studying at the Keskin Vocational High School of Kirikkale University, is tried to be measured on the basis of their personality traits.This study about the research subject is performed with a survey which is conducted on 283 students of Keskin Vocational High School who are still studying at undergraduate level. At the evaluation of entrepreneurial personality traits, scale is used which is published by Assoc. Prof. Kenan Oren and Asst. Prof. Mehmet Bickes’s in 16. volume of EASF Journal of Suleyman Demirel University at 2011.Other results of the survey attempted to reach, is specified as whether there is a positive relationship between “risk taking tendency and entrepreneurship” and “need of achievement and entrepreneurship” or not.